2017
DOI: 10.1039/c7ib00015d
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale study of the role of dynamin in the regulation of glucose uptake

Abstract: Glucose uptake in muscle cells in response to insulin is a fundamental mechanism for metabolism. The inability of cells to mobilize the specific glucose transporter GLUT4 is believed to be at least partially accountable for diseases, like diabetes, where cells do not respond to an insulin stimulus. In this work, a microchip is used to detect electrochemically glucose uptake from C2C12 myoblasts cultured on a patch of paper upon exposure to insulin. More importantly, the data suggest a new role for dynamin, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Additionally, the deleterious effects of NaCl are greater than those of sucrose at the same molarity 5 . Additional phenotypic results also revealed that high doses of glucose severely affect the motility of nematodes 14 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, the deleterious effects of NaCl are greater than those of sucrose at the same molarity 5 . Additional phenotypic results also revealed that high doses of glucose severely affect the motility of nematodes 14 .…”
Section: Introductionmentioning
confidence: 94%
“…L-Glucose is not biologically active, and this compound affects the nematode differently. Previous studies determined the different impacts of these two enantiomer compounds on lifespan 39 , motility 14 , the egg laying rate 40 , and nematode sensitivity 41 .…”
Section: Osmotic Influence On Embryo Developmentmentioning
confidence: 99%
“…2-DG transport -into Soleus and EDL muscles were assessed as described before (80). Electrochemical glucose sensing -Inspired by (81) we fabricated a microfluidic chip system using standard soft lithographic techniques. The chips were divided into a tissue chamber and a glucose sensing chamber connected by tubing.…”
Section: Glucose Uptake Measurementsmentioning
confidence: 99%
“…Next the fiber-containing paper patch were inserted into the tissue chamber and perifused with serum free DMEM containing 4 mM glucose for 3-5 minutes. Next, the glucose concentration in the perfusate was monitored during basal and insulin-stimulated conditions and ∆glucose was calculated as previously described (81). Colchicine and Noco treatment for 2h was achieved by preincubating the paper patches containing fibers in colchicine and Noco and keeping the drugs in the perfusate at all times after the assembly of the tissue chamber.…”
Section: Glucose Uptake Measurementsmentioning
confidence: 99%
“…Its high porosity facilitates wicking and makes it highly amenable to microfluidic applications and fluid handling . Its chemical inertness allows for the culture of cells, thus providing a robust substrate for three‐dimensional multicellular assays …”
Section: Introductionmentioning
confidence: 99%